2011
DOI: 10.1186/1475-2840-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Screening for left ventricular hypertrophy in patients with type 2 diabetes mellitus in the community

Abstract: BackgroundLeft ventricular hypertrophy (LVH) is a strong predictor of cardiovascular disease and is common among patients with type 2 diabetes. However, no systematic screening for LVH is currently recommended for patients with type 2 diabetes. The purpose of this study was to determine whether NT-proBNP was superior to 12-lead electrocardiography (ECG) for detection of LVH in patients with type 2 diabetes.MethodsProspective cross-sectional study comparing diagnostic accuracy of ECG and NT-proBNP for the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 30 publications
3
50
0
6
Order By: Relevance
“…ECG data can give information on LVH, and are useful to understand cardiac dysfunction and heart disease [29]. ECG observations from our study revealed R-wave enlargement, development of Q waves, prolonged QT interval, and ST segment depression in HFFD-fed mice.…”
Section: Discussionmentioning
confidence: 56%
“…ECG data can give information on LVH, and are useful to understand cardiac dysfunction and heart disease [29]. ECG observations from our study revealed R-wave enlargement, development of Q waves, prolonged QT interval, and ST segment depression in HFFD-fed mice.…”
Section: Discussionmentioning
confidence: 56%
“…12 Generally, black individuals have greater precordial QRS voltages than whites and many of the LVH criteria have higher sensitivity in detecting LVH in blacks and lower specificity compared with whites. 13,14 However, many of the criteria proposed like the Araoye for African blacks are yet to be validated and so far have offered no comparative advantage over the standard criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Further, LVH and cardiomyopathy in Fabry’s disease have been attributed to vitamin D deficiency due to less exposure to sunlight [29]. Diabetes, a chronic inflammatory disease, is a risk factor for LVH [30]. Reversal of LVH in diabetic rats [31] and attenuation of TNF-α expression by inhibition of nuclear factor-kappa beta (NF-κB/p65) signaling in hypertrophied rat hearts with vitamin D [32] suggest the role of vitamin D in reversal of LVH.…”
Section: Cardiac Diseasesmentioning
confidence: 99%